Artificial intelligence framework for MSME sectors with focus on design and manufacturing industries. (2022) - Sharma, Paawan; Shah, Jigarkumar; Patel, Reema
Abstract: Artificial Intelligence (AI) is gaining high popularity in multiple domains targeting different industries. Though initial adoption of AI was thought of as an enabler for automation in industries, but later it presented vast possibilities in innovation and design. Also, with advent of Industry 4.0 standards, AI emerged to play a big role in its adoption across different sectors of industries. Micro, Small and medium enterprises (MSMEs) with limited resources look upon AI as a tool for accelerating their growth. In India, the MSME sector although varies with different States, but dominantly includes textiles, machinery and parts, mining and quarrying, basic metal industries, electrical machinery and apparatus, transport equipment and parts, paper products and printing, food products, chemical and chemical products, leather, wood, rubber, plastic and other non-metallic mineral products, beverages and tobacco products. This paper proposes architectural framework and also provides probable applications of Internet of Things (IoT) and AI for design and manufacturing MSMEs of India.